The Attitude of the Christians of Allsaints Town Church Masindi-Kitara Diocese Towards Eucharist (2014–2024) - Christopher Munguaciel (Uganda Christian University, 2024)
The Eucharist, also known as Holy Communion or the Lord’s Supper, holds a central place in Christian worship and theology. This research paper aims to explore the attitude of Christians towards Eucharist. By analyzing Biblical teachings, historical development, and contemporary practices, this study seeks to shed light on the wide array of attitudes that Christians hold towards this Sacrament. This research investigates the potential factors influencing these attitudes, including theological traditions, historical context, cultural backgrounds, and personal experiences. The study finds that Church traditions, scriptural interpretations, and theological discourses play significant roles in forming and shaping Christians attitudes towards the Eucharist. To achieve the goal of this study, a comprehensive literature review was conducted, covering primary sources such as the Bible, early Church writings, and contemporary scholarly works.
Undergraduate Research